Optimalisasi Pemanfaatan Pajak dalam Perspektif Hukum Keuangan Negara: Antara Prinsip Keadilan Fiskal dan Akuntabilitas Publik - Wilma Silalahi; Gladwin Wijaya (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
Taxation is a fundamental instrument in the state financial system, serving as the primary source of revenue to fund governance and national development. This article discusses two key aspects: the legal framework for tax utilization under Law Number 17 of 2003 on State Finance and Law Number 7 of 2021 on the Harmonization of Tax Regulations, as well as the application of the principles of justice and accountability as mandated by Articles 23A and 23C of the 1945 Constitution. The study finds that both laws strengthen the legal and constitutional foundations for transparent, efficient, and equitable tax management. Tax utilization should aim to enhance public welfare through fiscal redistribution, public service funding, and social protection. The principle of justice emphasizes proportional contribution according to economic capacity, while accountability demands transparency and responsibility in every use of public funds. By implementing these principles, taxation becomes not only a fiscal tool but also a legal and moral instrument to promote clean governance, social justice, and sustainable welfare for the people.